Methods for fostering transdisciplinary research and co-design of agroecological solutions through structured Vision-to-Action (V2A) processes in multi-stakeholder spaces. - Fuchs, Lisa Elena; Bergamini, Nadia; Triomphe, Bernard (2025)
As food systems face multiple crises, globally and locally, new and alternative approaches to governing them are gaining momentum. Many of these approaches are conceptualized in terms of Multi-Stakeholder Platforms (MSPs), Innovation Platforms (IPs), and Living Labs (LLs), which typically focus on addressing local or territorial challenges in parallel to the broader systems within which they operate. Although these platforms differ, they all serve as spaces where different stakeholders actively seek to address collective action problems. Yet, despite their increasing popularity, specific and tested methods to foster actual transdisciplinary (problem-focused, solution-oriented, inclusive, reflexive) research and co-design in these configurations remain scarce. The CGIAR Agroecology Initiative (AE-I) facilitated the emergence of eleven agroecological living landscapes (ALLs) to foster agroecological transitions (AET) through the co-design of new production practices, value chain arrangements and business models, as well as improving the enabling environment, and achieving behavior changes. Drawing on explicit engagement principles, country teams established their respective ALLs by mapping stakeholders and defining functional boundaries. To ensure that agroecological solutions are identified based on a comprehensive understanding of the agri-food system context and are developed and scaled in response to local interests, priorities, and constraints, the AE-I team developed the Vision-to-Action (V2A) approach. Building on appreciative inquiry, Asset Based Community Development, back-casting, ex ante impact pathways, foresight, sustainability planning, and visioning approaches, V2A guides ALL stakeholders through the process of identifying a collective vision of what a desirable future would look like, defining transition pathways and behavior changes required, and developing action plans to support the AET process. The V2A process also comprises explicit and structured participatory monitoring, evaluation and learning (P-MEL) as an iterative process for continuous self-reflection and adaptive management. To support P-MEL, the V2A Transformation Map was developed to return data to ALL stakeholders in an accessible and visually appealing format. V2A also guides ALL stakeholders to negotiate strategic collaboration and partnerships, and provides entry points for external actors to support demand-driven change processes. V2A was implemented in all eleven ALLs of the AE-I, and served to collectively identify eleven context-specific multi-actor, multi-scalar, and multi-dimensional transition pathways. Over 11,000 persons were engaged in these ALLs, with impressive outcomes after only a few years. Our research illustrates that ALLs can function as organizational vehicles that foster co-learning and the co-design of innovations. Yet, their potential depends on the genuine application of participatory methods and approaches to all aspects of ALL functioning, including situational analysis – but, importantly, the design of context-specific solutions. The development of various guiding principles, including the engagement principles (Triomphe et al. 2022) and the V2A process (Triomphe et al. 2024), both of which are also featured in the broader ALL engagement toolkit (Voss et al. 2024), contribute to the growing body of methods that provide practical guidance for mobilizing communities to engage in inclusive and productive co-design of solutions in support of agroecological transformation.